Incidence and management of adverse events in patients with relapsed and/or refractory multiple myeloma receiving single-agent carfilzomib - Harvey RD (Dove Medical Press, 2014)
R Donald HarveyPhase 1 Clinical Trials Section, Winship Cancer Institute of Emory University, Atlanta, GA, USAAbstract: Carfilzomib, a selective proteasome inhibitor approved in the USA in 2012, is a single agent for relapsed and refractory multiple myeloma. Carfilzomib is administered as a 2–10-minute infusion on days 1, 2, 8, 9, 15, and 16 of a 28-day cycle at a starting dose of 20 mg/m2 for cycle 1 and a target dose of 27 mg/m2 thereafter. In the pivotal Phase II study (PX-171-003-A1), carfilzomib 20/27 mg/m2 provided durable responses in a heavily pretreated population with relapsed and refractory multiple myeloma (n=266), with an overall response rate of 22.9% and a median duration of response of 7.8 months. In an integrated safety analysis of four Phase II studies, common adverse events (32.7%–55.5%) included fatigue, anemia, nausea, thrombocytopenia, dyspnea, and diarrhea. Grade 3/4 adverse events were generally hematologic and included thrombocytopenia (23.4%), anemia (22.4%), and lymphopenia (18.1%). Serious adverse events included pneumonia (9.9%), acute renal failure (4.2%), pyrexia (3.4%), and congestive heart failure (3.4%). New or worsening peripheral neuropathy was infrequent (13.9% overall, 1.3% grade 3, no grade 4). This review discusses findings of the integrated safety analysis and provides practical experience from a single institution in managing treatment-related and disease-related adverse events. Individualized treatment with proactive management of side effects and complications allows patients with advanced multiple myeloma to remain on carfilzomib for extended periods.Keywords: carfilzomib, relapsed, refractory, myeloma, safety, adverse events, toxicity